2019
DOI: 10.5114/ait.2019.90921
|View full text |Cite
|
Sign up to set email alerts
|

Daily sedation interruption and mechanical ventilation weaning: a literature review

Abstract: Administration of sedatives is an integral part of intensive care unit (ICU) routine practice for a plethora of reasons: reduction of patient discomfort by providing anxiolysis, treating agitation but also facilitation of care, by increasing tolerance of the ventilator and preventing accidental removal of the endotracheal tube or other instrumentation (e.g. catheters, monitors and intravenous lines). Finally, sedation reduces metabolic demands during cardiovascular and respiratory instability [1]. Agents mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
5
0
2
Order By: Relevance
“…We also proved this when we used VAS and RS to evaluate patients. It is shown that patients with MV in the ICU are prone to emergence agitation during treatment, which can easily induce many adverse events and affect the treatment effect [ 19 ]. Our experimental results also further suggest that DEX has a good sedative effect, which can relieve the agitation of patients to a certain extent and improve the treatment compliance.…”
Section: Resultsmentioning
confidence: 99%
“…We also proved this when we used VAS and RS to evaluate patients. It is shown that patients with MV in the ICU are prone to emergence agitation during treatment, which can easily induce many adverse events and affect the treatment effect [ 19 ]. Our experimental results also further suggest that DEX has a good sedative effect, which can relieve the agitation of patients to a certain extent and improve the treatment compliance.…”
Section: Resultsmentioning
confidence: 99%
“…There are some general advantages of tracheostoma compared to endotracheal tubes that are already described in the Introduction, although these parameters are not necessarily dependent on early or late tracheotomy. Continuous sedation is, however, associated with numerous side effects, including bradycardia, hypotension, renal failure, respiratory depression and impaired cognition [ 26 ]. It is likely that tracheotomy is associated with a reduced need for sedatives compared to endotracheal tube treatment, which is also in line with the PP results of the current study showing that early tracheotomy implies fewer days of sedation compared to late tracheotomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, these treatments themselves can cause stress, pain, discomfort, and even complications (12). Ensuring the effectiveness of mechanical ventilation and other treatments and improving the comfort of patients in the ICU are the main purposes of analgesia and sedation treatment, and it is also an important measure to improve the safety of the treatment process (13,14). However, analgesia and sedation therapy itself may also increase the risk of death and the risk of complications for patients.…”
Section: Discussionmentioning
confidence: 99%